2014
DOI: 10.1126/science.1258138
|View full text |Cite
|
Sign up to set email alerts
|

Nidogens are therapeutic targets for the prevention of tetanus

Abstract: Tetanus neurotoxin (TeNT) is among the most poisonous substances on Earth and a major cause of neonatal death in nonvaccinated areas. TeNT targets the neuromuscular junction (NMJ) with high affinity, yet the nature of the TeNT receptor complex remains unknown. Here, we show that the presence of nidogens (also known as entactins) at the NMJ is the main determinant for TeNT binding. Inhibition of the TeNT-nidogen interaction by using small nidogen-derived peptides or genetic ablation of nidogens prevented the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 43 publications
4
78
0
1
Order By: Relevance
“…Since FGRF3 may undergo receptor-mediated endocytosis followed by long-range transport upon stimulation with its ligand, it might be able to mediate the uptake, sorting, and transport of BoNT/A along its trafficking route. Alternatively, BoNT/A could bind extracellular matrix (ECM) components at the NMJ as recently reported for TeNT [118], leading to its sorting to axonal signaling endosomes and transcytosis.…”
Section: Bont Receptorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Since FGRF3 may undergo receptor-mediated endocytosis followed by long-range transport upon stimulation with its ligand, it might be able to mediate the uptake, sorting, and transport of BoNT/A along its trafficking route. Alternatively, BoNT/A could bind extracellular matrix (ECM) components at the NMJ as recently reported for TeNT [118], leading to its sorting to axonal signaling endosomes and transcytosis.…”
Section: Bont Receptorsmentioning
confidence: 95%
“…We recently showed that TeNT interacts with specific ECM components at the NMJ to stimulate uptake of TrkB and formation of signaling endosomes [118]. In particular, the H C domain of TeNT (H C T) directly binds to both nidogen-1 and -2 and selectively targets NMJs containing high levels of nidogen-2.…”
Section: Tent Receptorsmentioning
confidence: 99%
“…Whereas Rab5 is essential for an early step in TeNT sorting, Rab7 plays an essential role in long-range axonal retrograde transport. Endocytosis of TeNT was also recently shown to require the extracellular matrix proteins, Nidogens, at the neuronal surface (37). The endocytosed TeNT-Nidogen complex is retrogradely transported into the cell body to elicit its toxic effects.…”
Section: Figmentioning
confidence: 99%
“…The endocytosed TeNT-Nidogen complex is retrogradely transported into the cell body to elicit its toxic effects. Inhibition of the TeNTNidogen interaction with small Nidogen-derived peptides or genetic ablation of Nidogens prevented the binding of TeNT to neurons and protected mice from TeNT-induced spastic paralysis (37).…”
Section: Figmentioning
confidence: 99%
“…Recent studies have indicated that CHIKV enters cells in vitro rapidly through clathrin-mediated endocytosis [65]. Our approach which is dependent on fusion to target cells and avoids the side effects of infection could be utilised to further isolate and elucidate the CHIKV entry receptor [66].…”
mentioning
confidence: 99%